Avoidance of primary site adjuvant radiotherapy following transoral robotic surgery: a cohort study. Issue 3 (11th January 2022) - Fradet, Laurent; Charters, Emma; Gao, Kan; Froggatt, Catriona; Palme, Carsten; Riffat, Faruque; Nguyen, Kevin; Wu, Raymond; Milross, Chris; Clark, Jonathan R.
Abstract: Background: Post‐operative radiotherapy (PORT) volumes and dose to target structures likely influence swallowing function and quality of life following transoral robotic surgery (TORS). The aim of this study is to analyse disease control and swallowing outcomes in patients undergoing TORS for oropharyngeal squamous cell carcinoma (OPSCC) to determine the impact of omitting the primary site from the PORT treatment volume. Methods: Prospectively collected data from patients that underwent TORS between March 2013 and April 2021 were reviewed. Patients were categorized into three groups: (1) no PORT, (2) PORT to the neck alone or (3) PORT to the primary site and neck. Survival curves were generated according to the Kaplan–Meier method and swallowing was assessed using the Functional Oral Intake Scale, Public Status Scale Head and Neck, MD Anderson Dysphagia Inventory and feeding tube/gastrostomy dependence. Results: A total of 121 patients underwent TORS, of which 103 met inclusion criteria with a median follow up of 2.6 years. No patients developed local recurrence. The 3‐year regional control rates were 90%, 100% and 100% for groups 1, 2 and 3, respectively. Disease‐specific survival was 97% over the study period. Patients that received PORT to both the primary site and the neck (group 3) had worse swallowing outcomes at 12 months. Conclusion: Following TORS for OPSCC, avoiding PORT to the primary site, in appropriately selected patients, appears to be oncologically safe and is associated with superior swallowing outcomes. Abstract : The aim of this study is to analyse disease control and swallowing outcomes in patients undergoing transoral robotic surgery for oropharyngeal squamous cell carcinoma to determine the effect of omitting the primary site from the postoperative radiotherapy treatment volume. Our results suggest avoiding postoperative radiotherapy to the primary site, in appropriately selected patients, appears to be oncologically safe and associated with superior swallowing outcomes.